Enhanced swelling and methylene blue adsorption of polyacrylamide‐based superabsorbents using alginate modified montmorillonite. Issue 6 (17th October 2013) - Qiu, Haixia; Qiu, Zhaoxia; Wang, Jialing; Zhang, Ruobing; Zheng, Fuyuan
ABSTRACT Polyacrylamide/sodium alginate modified montmorillonite (PAM/SA‐MMT) superabsorbent composites were synthesized by free‐radical polymerization under normal atmospheric conditions. They were characterized by X‐ray diffraction, scanning electron microscopy, and Fourier transform infrared spectroscopy (FTIR). Their water absorbency and methylene blue (MB) adsorption behaviors were studied. Compared with PAM/MMT composites, PAM/SA‐MMT composites demonstrated greater water absorbency (863 g g−1 in distilled water and 101 g g−1 in 0.9 wt % NaCl solution) and higher adsorption capacity of 2639 mg g−1 for MB. The adsorption behaviors of the composites showed that the isotherms and adsorption kinetics were in good agreement with the Langmuir equation and pseudo‐second‐order equation, respectively. FTIR analysis suggested that the MB adsorption of PAM/SA‐MMT composites via a mechanism combined electrostatic, H‐bonding and hydrophobic interaction. © 2013 Wiley Periodicals, Inc. J. Appl. Polym. Sci., 2014, 131, 40013.